The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5430/ijhe.v5n1p160
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Perceptions of Facebook-use in Higher Education

Abstract: This paper reports the complete process for and findings resulting from an individual-led research project entitled An Investigation into Perceptions of Facebook-use in Higher Education. The aim of the research project was primarily to investigate current perceptions of using Facebook as a means for interaction between students and lecturers at university level. Findings are based on data collected from two sample populations (students and lecturers) using qualitative research methodology. Tentative findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Firstly, those students who spent most of their time online pursuing leisure activities. This student type has a greater online social presence, and this allows them to develop a more active and cohesive form of communication in group and collaborative learning processes (Armellini & De Stefani, 2015;Dickie & Meier, 2015;Ellefsen, 2015;Garrison, 2011;Wang, Woo, Quek, Yang, & Liu, 2012). Secondly, those students who spent hardly any time on the internet searching for information or doing academic work, and who used the internet mainly for leisure and entertainment (Sharma & Shukla, 2016;Sultan & Christian, 2014;Valkenburg, Peter, & Schouten, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, those students who spent most of their time online pursuing leisure activities. This student type has a greater online social presence, and this allows them to develop a more active and cohesive form of communication in group and collaborative learning processes (Armellini & De Stefani, 2015;Dickie & Meier, 2015;Ellefsen, 2015;Garrison, 2011;Wang, Woo, Quek, Yang, & Liu, 2012). Secondly, those students who spent hardly any time on the internet searching for information or doing academic work, and who used the internet mainly for leisure and entertainment (Sharma & Shukla, 2016;Sultan & Christian, 2014;Valkenburg, Peter, & Schouten, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…More informal digital platforms may also be used for engaging students in group learning activities in the classroom, such as Facebook and Twitter (Tess, 2013). These sites can be used as an alternative to the LMS as these may be platforms that students are already comfortable using in their personal lives (Duncan & Barczyk, 2015;Ellefsen, 2016). However, the educational use of these sites also has associated issues, such as possibilities for distraction and concerns around privacy (Flanigan & Babchuk, 2015;Selwyn, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Its high rate of adoption and popularity among students makes it more relevant for education. Its dynamic interaction has enormous potential to use as an education tool (e.g., Sheldon, 2015;Ellefsen, 2016;Dabbagh & Kitsantas, 2012;Draskovic et al, 2013). Moreover, the educators have enough potential to grape the opportunities that SM offers through its dynamic tools and capability to engaged students (Moran et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It could be claimed that SM platforms bring a radical change in the field of ethic, art, culture, economics, science, and education. Moreover, the use of SM platforms is highly appreciated and showing a growing trend in the field of higher education (Kassens-Noor, 2012;Taylor et al, 2012;Ellefsen, 2016 Although SM presented more effective ways of learning for scholars. However, it has been observed that lecturers are not share the same level of enthusiasm because it looks less formal communication platform (Draskovic et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation